Monotheism and the suffering of animals in nature - Southgate, Christopher (Cambridge elements. Elements in religion and monotheism, 2023)
This Element concerns itself with a particular aspect of the problem posed to monotheistic religious thought by suffering, namely the suffering of non-human creatures in nature. It makes some comparisons between Judaism, Christianity, and Islam, and then explores the problem in depth within Christian thought. After clarification of the nature of the problem, the Element considers a range of possible responses, including those based on a fall-event, those based on freedom of process, and those hypothesising a constraint on the possibilities for God as creator. Proposals based on the motif of self-emptying are evaluated. Two other aspects of the question concern God's providential relationship to the evolving creation, and the possibility of resurrection lives for animals. After consideration of the possibility of combining different explanations, the Element ends its discussion by looking at two innovative proposals at the cutting-edge of the debate.